"Chocolate City, Rest in Peace": White Space‐Claiming and the Exclusion of Black People in Washington, DC. (28th August 2019) - Helmuth, Allison Suppan
Abstract: Urban sociologists and gentrification scholars have long been interested in examining the combination of structural and micro‐level forces that result in the displacement and exclusion of low‐income residents from changing neighborhoods. However, the types of everyday activities and the social and spatial practices that exclude residents who remain in these neighborhoods are an understudied part of the gentrification story. How are exclusive spaces created? What are the specific social processes that lead to exclusive space? I draw on in‐depth interviews and ethnographic fieldwork to examine how white residents in a historically black neighborhood claim space through their everyday actions and interactions. These space‐claiming practices are at times subtle and at times overt, but often draw on a repertoire of physical, mental, and social practices that combine to create spaces that exclude black people—including long‐term black residents, black gentrifiers, and black visitors to the neighborhood—from public space.